International Price Relationship and Volatility Transmission Between Stock Index and Stock Index Futures - ArIsmail bin Ahmad; Fahmi bin Abdul Rahim (Economic Journal of Emerging Markets, 2009)
This study investigates the international price relationship and volatility transmissions betweenstock index and stock index futures of Malaysia, Hong Kong and Japan. Vector Autoregression(VAR) GJR-GARCH model was applied to the nine years daily price. Japanesemarkets are the main information producer to the market price changes. International marketinterdependence only affected the domestic volatility transmission of spot and futuresmarket in Hong Kong. Asymmetric effects exist in all markets and the volatility persistence ineach market is high. Finally, the overall conditional correlation estimates for spot and futuresmarkets are higher in the unrestricted model form compared to the restricted modelform.Keywords: spot-futures, lead-lags, volatility, VAR GJR-GARCH, Asian financial markets